THE LOGICAL STRUCTURE OF LINGUISTIC THEORY - Shaheen, Ranya Ahmed Rashid; Alhadi, Abdelrahman Mudawi Abdelrahim (Journal of Humanities & Social Sciences, 2021)
The object of inquiry in Linguistics is the human ability to acquire and use a natural language, and the goal of linguistic theory is an explicit characterization of that ability. Looking at the communicative abilities of other species, it becomes clear that our linguistic ability is specific to our species, undoubtedly a product of our biology. But how do we go about determining the specifics of this Language faculty? _here are two primary ways in which we infer the nature of Language from the properties of individual languages: arguments from the Poverty of the Stimulus, and the search for universals that characterize every natural language. Arguments of the first sort are not easy to construct (though not as difficult as sometimes suggested), and apply only to a tiny part of Language as a whole. Arguments from universals or typological generalizations are also quite problematic. In phonology, morphology, and syntax, factors of historical development, functional underpinnings, limitations of the learning situation, among others conspire to compromise the explanatory value of arguments from observed cross-linguistic regularities. Confounding the situation is the likelihood that properties found across languages as a consequence of such external forces have been incorporated into the Language faculty evolutionarily through the ‘Baldwin Effect.’ _e conflict between the biologically based specificity of the human Language faculty and the difficulty of establishing most of its properties in a secure way cannot, however, be avoided by ignoring or denying the reality of either of its poles.